VP1, the major capsid protein of the mouse polyomavirus, binds microtubules, promotes their acetylation and blocks the host cell cycle - Horníková, Lenka; Fraiberk, Martin; Man, Petr; Janovec, Václav; Forstová, Jitka (The FEBS journal, 2017)
VP1, the major structural protein of the mouse polyomavirus (MPyV), is the major architectural component of the viral capsid. Its pentamers are able to self-assemble into capsid-like particles and to non-specifically bind DNA. Surface loops of the protein interact with sialic acid of ganglioside receptors. Although the replication cycle of the virus, including virion morphogenesis, proceeds in the cell nucleus, a substantial fraction of the protein is detected in the cytoplasm of late-phase MPyV-infected cells. In this work, we detected VP1 mainly in the cytoplasm of mammalian cells transfected with plasmid expressing VP1. In the cytoplasm, VP1-bound microtubules, including the mitotic spindle, and the interaction of VP1 with microtubules resulted in cell cycle block at the G2/M phase. Furthermore, in the late phase of MPyV infection and in cells expressing VP1, microtubules were found to be hyperacetylated. We then sought to understand how VP1 interacts with microtubules. Dynein is not responsible for the VP1-microtubule association, as neither overexpression of p53/dynamitin nor treatment with ciliobrevin-D (an inhibitor of dynein activity) prevented binding of VP1 to microtubules. A pull-down assay for VP1-interacting proteins identified the heat shock protein 90 (Hsp90) chaperone, and Hsp90 was also detected in the VP1-microtubule complexes. Although Hsp90 is known to be associated with acetylated microtubules, it does not mediate the interaction between VP1 and microtubules. Our study provides insight into the role of the major structural protein in MPyV replication, indicating that VP1 is a multifunctional protein that participates in the regulation of cell cycle progression in MPyV-infected cells.
Keywords: chaperone Hsp90; mléčné žlázy zvířat; exprese genu; Humans; HeLa buňky; proteiny tepelného šoku HSP90; Cell Nucleus; Gene Expression; Mammary Glands, Animal; Host-Pathogen Interactions; Protein Binding; interakce hostitele a patogenu; Acetylation; acetylace; Female; virion; kontrolní body fáze G2 buněčného cyklu; Capsid Proteins; epitelové buňky; buněčné jádro; lidé; HEK293 Cells; plazmidy; zvířata; Microtubules; myši; cell cycle arrest; buňky NIH 3T3; Polyomavirus; mikrotubuly; Mice; HSP90 Heat-Shock Proteins; transfekce; NIH 3T3 Cells; Epithelial Cells; ženské pohlaví; Virion; HeLa Cells; VP1; HEK293 buňky; Cytoplasm; vazba proteinů; virové plášťové proteiny; cytoplazma; Transfection; Animals; microtubules; Plasmids; mouse polyomavirus; G2 Phase Cell Cycle Checkpoints